Challenges faced in daily life by persons with type 2 diabetes: A meta-synthesis. (September 2019) - Inga-Britt, Lindh; Kerstin, Blomqvist
Objectives: To derive improved understanding of the implicit meanings of challenges in daily life from the perspective of persons with type 2 diabetes. Methods: A meta-synthesis was conducted with an interpretive and constructivist approach. Four databases were searched for articles published between 2007 and 2011, producing 37 articles for analysis. Van Deurzen's life world theory was applied as an analytic grid. Results: Challenges in daily life with type 2 diabetes could be understood as living in a tension between opposing forces, implying a struggle with inevitable paradoxes: living in the present and for the future, trusting oneself while relying on others, and being normal while feeling changed and different. Discussion: This synthesis adds knowledge to previous understanding of living with type 2 diabetes, revealing the complexity of daily life when struggling with a lifelong illness. Person-centred care could be used to understand what challenges diabetes may cause in family and working life and the ambivalent feelings the illness can lead to. Future research is needed to implement and evaluate a person-centred care in practice. Since new qualitative research is continuously added to this topic, metasyntheses should be undertaken regularly.